Ayurvedic Strategies for Managing Non-alcoholic Fatty Liver Disease: A Holistic Approach - kumar mishra , Rohit; gupta , Sneha; antiwal, Meera (International Research Journal of Ayurveda & Yoga, 2025)
Metabolic disorders are now widespread even among seemingly healthy individuals. Non-alcoholic fatty liver disease (NAFLD) is one of them, NAFLD is a spectrum of liver disorders characterized by excessive fat accumulation in the liver, unrelated to alcohol consumption. It can progress from simple steatosis to non-alcoholic steatohepatitis, potentially leading to cirrhosis. NAFLD is closely linked to metabolic syndrome, obesity, and insulin resistance. NAFLD doesn’t directly align with any single Yakrit vikara (liver disorder) described in Ayurvedic classical texts.